Asymetric oxidation reactions catalyzed by chiral substituted polymers / nanoclusters; synthesis of 6-(dimethylamino)-2-phenylisoindolin-1-one derivative. - Hao, Bo (Kansas State University, 2018)
The discovery of new methodologies to advance the fields of synthetic organic, nanoclusters, and polymer chemistry is critical in the asymmetric synthesis of organic compounds. Particularly, catalytic asymmetric oxidation reactions are economic. The oxidation reactions provide chiral molecules and additional functionality onto the molecules for functional group manipulation. New kinds of polymers, namely chiral-substituted poly-N-vinylpyrrolidinones (CSPVPs), stabilize the bimetallic nanoclusters such as Pd/Au or Cu/Au and induce chirality. These chiral polymers wrap around the nanometer-sized (~3 nm) bimetallic nanoclusters and catalyze a number of enantioselective oxidation reactions using oxygen or hydrogen peroxide as the oxidant. Cycloalkanediols were asymmetrically oxidized by 1 atm of oxygen gas to yield the corresponding hydroxyl ketone under the catalysis of Pd/Au (3:1) – CSPVP nanoclusters. Alkenes were oxidized by Pd/Au (3:1)-CSPVP nanoclusters under 2 atmospheric of oxygen in water to give the syn-dihydroxylated products in high chemical and excellent optical yields. Various cycloalkanes underwent regio- and enantio-selective C-H oxidation with Cu/Au (3:1)-CSPVP and 30% hydrogen peroxide to produce the corresponding chiral oxo-molecules in very good to excellent chemical and optical yields. We further discovered an enantioselective desymmetrization of , -dialkenyl-alkanols and , -dialkenyl-amino acid ethyl esters to give chiral disubstituted lactones and lactams, respectively. A number of medium-sized natural products and drugs were also oxidized regioselectively to give the corresponding mono-oxygenated products. A broad-spectrum predictive C-H oxidation of complex molecules is possible. Chapter 1 mainly discussed the synthesis and characterization of the new classes of chiral substituted PVP and bimetallic nanoclusters. Chapter 2 focus on various kind of oxidation reactions by the catalysis of CSPVP stabilized bimetallic nanoclusters. Among various bioluminescence assays, firefly luciferase based bioluminescence assays are popular due to their high specific activity, low background noise and ease of use. However, it has been found that some aromatic carboxylic acid substantially inhibited the firefly luciferase reporter enzyme’s activity. In order to study firefly luciferase inhibition and the proteins associated with inhibition mechanism, we designed two 6-(dimethylamino)-2-phenylisoindolin-1-one derivatives as probe molecules. The synthesis of one probe molecule is discussed in Chapter 3 and the further investigation of its inhibitory activity on firefly luciferase is being conducted by our collaborate.
Keywords: Bimetallic nanoclusters; Chiral polymer; Asymmetric oxidation; 6-(dimethylamino)-2-phenylisoindolin-1-one